2017
DOI: 10.3748/wjg.v23.i20.3675
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NDC80 in human hepatocellular carcinoma

Abstract: AIMTo investigate the role of nuclear division cycle (NDC)80 in human hepatocellular carcinogenesis.METHODSNDC80 gene expression was analyzed by real-time reverse transcription polymerase chain reaction in 47 paired hepatocellular carcinoma (HCC) and adjacent tissues. The HCC cell line SMMC-7721 was transfected with lentivirus to silence endogenous NDC80 gene expression, which was confirmed by real-time polymerase chain reaction and western blotting. The effects of NDC80 silencing on SMMC-7721 cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 30 publications
6
47
0
Order By: Relevance
“…The mitotic regulator NDC80 is highly expressed in various human malignancies, including hepatocellular carcinoma, colon cancer and osteosarcoma (33)(34)(35). NDC80 is also called Hec1, and its complexes together with NUF2 component of NDC80 kinetochore complex (NUF2), SPC24 component of NDC80 kinetochore complex (SPC24) and SPC25 component of NDC80 kinetochore complex (SPC25) participate in the spindle assembly checkpoint and regulation of mitosis and chromosome segregation (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…The mitotic regulator NDC80 is highly expressed in various human malignancies, including hepatocellular carcinoma, colon cancer and osteosarcoma (33)(34)(35). NDC80 is also called Hec1, and its complexes together with NUF2 component of NDC80 kinetochore complex (NUF2), SPC24 component of NDC80 kinetochore complex (SPC24) and SPC25 component of NDC80 kinetochore complex (SPC25) participate in the spindle assembly checkpoint and regulation of mitosis and chromosome segregation (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…It forms a heterotetramer complex with proteins SPC24, SPC25 and NUF2, and the complex has been known to involve in spindle assembly checkpoint signaling, detecting the unaligned chromosomes to assure the correct segregation of chromosomes. Aberrant expression of NDC80 has been reported in several other tumors [38][39][40][41][42] , for instance osteosarcoma, hepatocellulcar carcinoma, colorectal cancer and breast cancer, indicating its potential as a newly bio target.…”
Section: Discussionmentioning
confidence: 99%
“…HCC is a leading cause of cancer-associated mortality worldwide, and tumor recurrence and metastasis are major factors that contribute to the poor prognosis of HCC patients (29,30). Previous studies have confirmed that protein ubiquitination serves multiple roles in different biological processes.…”
Section: Discussionmentioning
confidence: 99%